KEABSAHAN WASIAT MELEBIHI 1/3 BAGIAN HARTA PUSAKA DITINJAU DARI HUKUM ISLAM DAN HUKUM ADAT MINANGKABAU - Siti Intan Sekarieva, Djanuardi, Hazar Kusmayanti (Normative Jurnal Ilmiah Hukum, 2020)
A testament or will is a way to distribute inheritance. The implementation of a testament in Indonesia is based on the Indonesian Civil Code, the Compilation of Islamic Law, and Customary Law. In the practical situations, there are a lot of confusions regarding the validity of a testament that exceeds 1/3 of inheritance, especially in the Indigeneous Minangkabau People. In the perspective of Islamic law, the testament that exceeds 1/3 of inheritance is valid by the consent of the heirs, but if the heirs do not agree with it then the testament must be enforced only up to the limit of 1/3 portion of the inheritance left by them. Whereas the customary law of Minangkabau determines that the validity of a testament must be based by the type of the inheritance. In the perspective of Minangkabau Customary Law, the inheritance that is classified as harta pusaka tinggi is invalid because it is not owned collectively, meanwhile the testament that is classified as harta pusaka rendah should follows the rules of Islamic Law (Faraid) which has regulated that a testament that exceeds 1/3 of inheritance is valid if it has been agreed by all of the heirs, but if the heirs do not agree with it then the valid testament is only 1/3 portion of the inheritance because the rest of them are the assets of the heirs.